Successful factors of career development among employees at Bernama, Kuala Lumpur / Farrah Azrah Mohd Rahim - Mohd Rahim, Farrah Azrah (Faculty of Business and Management, 2019)
Employee is the major role-player to ensure that organization’s goals and objective is achieved. Employers play an important role to ensure that employees had achieved something big for their career, thus career development is vital for organization, employers as well employees to enhance everyone working performances and can contribute to organizations. Training and Development, Career Planning and Career Counselling are the major predictors has been identified as the variables that influence Career Development. Therefore, the purpose of this research is to investigate the determinants of Career Development among employees at Bernama, Kuala Lumpur. This research was aimed to achieve the following objectives; investigate the relationship of training and development, career planning and career counselling towards career development among employees. This research also used convenience sampling techniques to obtain the data from the respondents. Total population of this research are 210 employees from the BNC (Bernama News Channel) with sample size of 136 respondents. Likert scale was used to collect data from respondents using online survey (Google Docs). The Cronbach’s Alpha of the questionnaire a = 0.939 which shows the instrument is reliable. Moreover, the results shows that career counselling is not significant but has positive relationship with career development. While training and development and career planning are significance and has positive relationship with career development. Therefore, the result will help the company to enhance employees’ career development in order to increase performance and productivity.